Conceptions of dignity in the Charlie Gard, Alfie Evans and Isaiah Haastrup cases - Jonas, Monique (Bioethics, 2020)
In 2017 and 2018, the English courts were asked to decide whether continued life-sustaining treatment was in the best interests of three infants: Charlie Gard, Alfie Evans and Isaiah Haastrup. Each infant had sustained catastrophic, irrecoverable brain damage. Dignity played an important role in the best interests assessments reached by the Family division of the High Court in each case. Multiple conceptions of dignity circulate, with potentially conflicting implications for infants such as Charlie, Alfie and Isaiah. The judgements do not explicate the conceptions of dignity upon which they rely. This article reconstructs the conceptions of dignity invoked in these judgements, finding that a broadly Kantian, agential conception dominates, under which human dignity requires the prospect of agency. This conception is situated within the broader body of thought on dignity, and the potentially adverse implications of applying the reconstructed conception in best interests assessments for infants with severely restricted consciousness are discussed.